2022
DOI: 10.1002/admi.202101679
|View full text |Cite
|
Sign up to set email alerts
|

Organic Field‐Effect Transistors Based on Ternary Blends Including a Fluorinated Polymer for Achieving Enhanced Device Stability

Abstract: The stability of organic semiconductors (OSCs) is strongly hampered by the presence of water molecules. One approach that has been proved to lead to organic field‐effect transistors with an enhanced performance is the use of blends of OSCs with insulating binding polymers. In this work, the fabrication of OSC thin films based on polymeric ternary blends including a hydrophobic fluorinated polymer is reported as a novel route to engineer long‐term reliable organic field‐effect transistors (OFET) devices. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…OFETs based on the parent compound TIPS‐pentacene fabricated following the same methodology (i.e., blended with PS and deposited by BAMS, hereafter TIPS:PS) led to device mobilities in the range 0.5‐1 cm 2 V –1 s –1 and a density of traps of (9.2 ± 2.8) 10 11 eV –1 cm –2 . [ 13,16,26,49 ] In comparison, TMTES films show a field‐effect mobility between two and four times higher, that we ascribe to the more favorable 2D herringbone crystal packing and also to the lower presence of interfacial hole‐traps.…”
Section: Resultsmentioning
confidence: 81%
“…OFETs based on the parent compound TIPS‐pentacene fabricated following the same methodology (i.e., blended with PS and deposited by BAMS, hereafter TIPS:PS) led to device mobilities in the range 0.5‐1 cm 2 V –1 s –1 and a density of traps of (9.2 ± 2.8) 10 11 eV –1 cm –2 . [ 13,16,26,49 ] In comparison, TMTES films show a field‐effect mobility between two and four times higher, that we ascribe to the more favorable 2D herringbone crystal packing and also to the lower presence of interfacial hole‐traps.…”
Section: Resultsmentioning
confidence: 81%
“…Comparing the position of the first (001) peak, small shifts can be distinguished, which might be indicative of some lattice strain caused by the different binding polymers. 45,46 The OSC thin films were investigated as active layer in OFETs, in a bottom gate bottom contact structure, with the aim at exploring how the binder polymer affects their electrical performance (see Figure 3a for the device configuration). The transfer characteristics for all the devices in the saturation regime are shown in Figure 3b-e (see Figure S4 for the output characteristics), and the parameters extracted are collected in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…High-uniformity and high-qualitycrystalline film led to fieldindependent mobility with low dispersion. In 2022, Tamayo et al [113] found that addition of poly(pentafluorostyrene)(PFS) in blends of small molecules/insulator polymer is an effective strategy to improve the long-term reliability of OTFTs. Ultrahigh hydrophobicity of PFS acted as barrier against humidity, which reduced charge traps and deterioration of the crystalline films.…”
Section: Post-treatmentmentioning
confidence: 99%